2023
DOI: 10.1038/s41388-023-02624-7
|View full text |Cite
|
Sign up to set email alerts
|

PRMT6-CDC20 facilitates glioblastoma progression via the degradation of CDKN1B

Abstract: PRMT6, a type I arginine methyltransferase, di-methylates the arginine residues of both histones and non-histones asymmetrically. Increasing evidence indicates that PRMT6 plays a tumor mediator involved in human malignancies. Here, we aim to uncover the essential role and underlying mechanisms of PRMT6 in promoting glioblastoma (GBM) proliferation. Investigation of PRMT6 expression in glioma tissues demonstrated that PRMT6 is overexpressed, and elevated expression of PRMT6 is negatively correlated with poor pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
1
13
1
Order By: Relevance
“…S5), and ChIP-qPCR results showed that PRMT6 inhibits the transcriptional regulation of TRAF6 through H3R2me2a at the TRAF6 promoter. The regulatory mark of PRMT6-mediated asymmetric dimethylation of histones is a well-known mechanism that can either activate or repress gene expression [50], and our previous study demonstrated that PRMT6 can enhance the transcription of CDC20 in GBM cells via H3R2me2a [19]. However, these ndings appear to be contradictory to the results presented here.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…S5), and ChIP-qPCR results showed that PRMT6 inhibits the transcriptional regulation of TRAF6 through H3R2me2a at the TRAF6 promoter. The regulatory mark of PRMT6-mediated asymmetric dimethylation of histones is a well-known mechanism that can either activate or repress gene expression [50], and our previous study demonstrated that PRMT6 can enhance the transcription of CDC20 in GBM cells via H3R2me2a [19]. However, these ndings appear to be contradictory to the results presented here.…”
Section: Discussioncontrasting
confidence: 99%
“…8). Moreover, in our previous studies, it has been con rmed that PRMT6 silencing in GBM cells signi cantly inhibits the growth of transplanted tumors and signi cantly prolongs the survival time of xenograft mice [19]. Therefore, our study demonstrates that PRMT6 could contribute to the proliferation and invasiveness of GBM cells in vivo, which is the main reason why PRMT6 is identi ed as an oncogene in glioma.…”
Section: Prmt6 Contributes To Gbm Invasion In Vivosupporting
confidence: 58%
See 2 more Smart Citations
“…To detect cell proliferation ability, 1 × 10 3 stable transfected MKN45 and HGC27 cells were cultured in 96 well plates and 6 well plates for 6 and 15 days, respectively. As mentioned previously [35], cell viability was detected by cell counting and MTT assay. After staining with crystal violet, the scanning plate clone formation assay was used, and the absorption rate of 560 was nally measured using absolute ethanol to measure nm for statistical analysis.…”
Section: Cell Proliferation Detection and Plate Colony Formation Expe...mentioning
confidence: 99%